2009
DOI: 10.1056/nejmc0902799
|View full text |Cite
|
Sign up to set email alerts
|

Mirror Therapy for Chronic Complex Regional Pain Syndrome Type 1 and Stroke

Abstract: T h e ne w e ngl a nd jou r na l o f m e dic i ne n engl j med 361;6 nejm.org august 6, 2009 634 lost extensibility), and a knee with limited mobility. 2 The minimally invasive approach is appropriate for most but not all knees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(106 citation statements)
references
References 5 publications
5
85
0
16
Order By: Relevance
“…Interestingly, participants receiving motor imagery treatment had increased pain levels (compared to baseline pain). Similar findings were reported by Cacchio et al 2 , in which six out of eight participants experienced increased pain levels following four weeks of motor imagery. However, Cacchio et al 2 found no difference between motor imagery and covered mirror therapy (five of eight participants had increased pain in covered mirror therapy group).…”
Section: Motor Imagerysupporting
confidence: 90%
See 4 more Smart Citations
“…Interestingly, participants receiving motor imagery treatment had increased pain levels (compared to baseline pain). Similar findings were reported by Cacchio et al 2 , in which six out of eight participants experienced increased pain levels following four weeks of motor imagery. However, Cacchio et al 2 found no difference between motor imagery and covered mirror therapy (five of eight participants had increased pain in covered mirror therapy group).…”
Section: Motor Imagerysupporting
confidence: 90%
“…Four authors were contacted to gain additional information required to calculate the effect size of their intervention 2,3,23,25,26,28 . One author could not be contacted, thus the effect size for this study could not be calculated 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations